(untitled) (The Peerian Journal, 2024)
In the article, mining enterprises based on local mineral and raw material resources of the Republic of Karakalpakstan are considered as an example of TebinBulak metals iron ore enterprises. Today, one of the main directions of the innovative development of the economy and the deepening of market reforms is the improvement of the branch structure of the industry, that is, the diversification of the regional industry is gaining major importance. The territories of the Republic of Uzbekistan are considered to have great natural, land, mineral and labor potential. The implementation of these tasks allows to ensure economic balance in the republic’s territories, eliminate socio-economic and environmental problems, and create conditions for raising the standard of living of the population. Despite the fact that iron ore extraction plants using flotation and magnetic separators at the TebinBulak metals mine of the Republic of Karakalpakstan have a large mining capacity, they purchase raw materials from other regions, therefore, the task of minimizing waste is the prospect of strengthening their raw material base. The technology for improving the quality of titanium-magnetite concentrate, the main composition of iron ores, was proposed, which consists in separating the ore into two technological grades - rich and poor, and then separately grinding and concentrating the grades in separate sections. Thanks to this technological scheme, the ore is divided into easily concentrated and hard concentrated varieties at the concentration stage